Intersectoral Linkages and Spillover Effects in South Sumatra’s Economy: Evidence from the 2016 Interregional Input–Output Table and 2024 Input–Output Table - Marpaleni; Mardiana; Puspita, Anggi Dwi; Rama, Indhira Putri (Proceedings of The International Conference on Data Science and Official Statistics, 2025)
This study examines South Sumatra’s economic structure using interregional input– output analysis to identify key sectors and quantify spillover effects. A dual-dataset approach employs the 2016 IRIO table for interprovincial trade dynamics and the 2024 IO table for current sectoral analysis. Results indicate a domestically oriented economy, with 88.45% of supply met by internal production. Manufacturing and construction emerge as central hubs with strong intersectoral linkages, supported by agriculture and mining as upstream suppliers. Interregional trade is concentrated with nearby Sumatran provinces and Java’s industrial centers. Spillover effects benefit Jambi, Bengkulu, and Banten, while feedback effects show dependency on Java. Output multipliers highlight electricity and gas as key growth drivers, whereas agriculture and real estate contribute most to local income. These patterns reveal a structural divergence between growth and inclusivity. To address this, the study recommends a dual-track strategy: scale up manufacturing and energy to drive aggregate output, while modernizing agriculture and highvalue services to support income distribution. Strengthening interprovincial corridors and deepening local supply chains can further enhance resilience and expand the province’s role in national development.